Embodiment and Social Distancing: Performances - Charlotta Ruth; Ellen Kress; Josiah Pearsall; Kristine Samson; Lasse Emil Mouritzen; Shabari Rao (Journal of Embodied Research, 2020)
A collection of five video essays on embodiment and social distancing, with a focus on performances. ELLEN KRESS, “Rest is Resistance: Embodied Reflections of the Retraction Period in the Creative Process” (00:10): This video essay contemplates the role that rest performs in my own creativity, connecting the labor movement, technology and the radical act of restorative rest. LASSE MOURITZEN AND KRISTINE SAMSON, “Pandemic Encounters” (05:34): As social distance became a daily routine, urban lives changed into sites of strange encounters, negotiating proximity and presence anew. JOSIAH PEARSALL, “I All Occur Within Arm’s Reach” (10:24): This video performance from April and May 2020 explores my embodied position in an isolated and constrained world; my world exists within the frame of a desk and a computer. SHABARI RAO, “Nothing to Show” (15:45): We are constantly redrawing and rediscovering our sense of self through feedback (intended and unintended) that we receive through physically sharing space with different people in a variety of environments. With social distancing, that range of environments is severely and suddenly restricted. What happens to my sense of self in these circumstances? How do I know who I am? What do I have to show the world and my self to confirm my sense of self? CHARLOTTA RUTH, “What is liveness and what can it be?” (19:59): Rethinking Alfred Schütz’s essay “On multiple realities” for online to offline existence.